Macrophyte habitat architecture and benthic-pelagic coupling: Photic habitat demand to build up large P storage capacity and bio-surface by underwater vegetation - Teubner, Katrin; Teubner, Irene E.; Pall, Karin; Tolotti, Monica; Kabas, Willi; Drexler, Silke-Silvia; Waidbacher, Herwig; Dokulil, Martin T. (Frontiers in Environmental Science, 2022)
Macrophytes play an important role in shallow lakes if large standing crop can be achieved. Here we stress the role of submerged macrophytes for benthic-pelagic coupling in the shallow oxbow lake Alte Donau (Austria) during restoration triggered by sufficient light availability (12% surface ambient light, photic>12% depth, zoptimum) in both, the benthic and the pelagic habitat. Focusing on zoptimum, rather than on minimum light requirement (euphotic depth), seemed to be more meaningful to follow the macrophyte development. After phosphate precipitation treatment, the photic>12% pelagic habitat accounted for more than half of the total water volume in summer, while the achievement of the same photic>12% conditions for half of the total sediment surface area was delayed by 8 years. A delay of light exposure on the lake bottom area compared to the lake water volume is given by the basin morphometry, but the time span that is required for passing this delay depends on the efficiency of restoration measures. The 8-year delay for Alte Donau means that lake restoration focusing on macrophyte re-establishment was difficult to stimulate due to insufficient light exposure at the lake bottom. A further increase of photic>12% conditions to more than 3/4 size of both pelagic and benthic habitat, however, eventually stimulated sustained macrophyte growth. With the onset of this large macrophyte biomass yield, the phosphorus storage pool of submerged macrophytes exceeded the annual peak concentration of total phosphorus of the whole lake water by about one order of magnitude for the first time. Further, the submerged macrophyte bio-surface exceeded the size of lake bottom surface, also by about one order of magnitude. Our results support that macrophytes can act as a significant sink of phosphorus by retaining this nutrient at least during the growing season. We further see the immensely large macrophyte bio-surface as a vast spatial dimension for an additional habitat for freshwater biota. Therefore, we conclude that mature submerged macrophyte formations need to be considered not only as biomass yield, but create a unique macrophyte habitat architecture as a third main component in the network between benthic (lake bottom) and pelagic (lake water) habitat.